NONLINEAR SCHRÖDINGER EQUATIONS ON SUPER SYMMETRIC SPACES RELATED TO LIE SUPERALGEBRAS A(m, n) - Ahmet, Canoḡlu; Bahri, Güldoḡan; Selâmi, Salihoḡlu (World Scientific Pub Co Pte Lt, 1991)
We obtain new integrable coupled nonlinear partial differential equations by assuming that the soliton connection has values in the Lie superalgebras A(m, n). These equations are coupled nonlinear Schrödinger equations on various super symmetric spaces.
Keywords: Invariance and symmetry properties for PDEs on manifolds; Superalgebras; NLS equations (nonlinear Schrödinger equations); Lie superalgebras; Kac-Moody algebras; soliton